(untitled) (Revista Inclusiones, 2020)
The paper reopens a discussion of what a concept as a dynamic phenomenon poses, bringing its structure and contents into the limelight. By defining the dynamic essence of the concept we shed some light on the mechanisms of the language manifestation of this mental unit. The paper gives an overview of the way the concept ‘Christian Spirituality’ is defined. Much emphasis is paid to the features of the verbal representation of the concept ‘Christian Spirituality’.